FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI SAYURAN DI KABUPATEN LABUHANBATU - Khairul Rizal (UNIVERSITAS LABUHANBATU, 2019)
This study aims to determine the factors that influence the level of income, to determine the level of profitability of vegetable farming and to find out whether the farming is feasible to run. This study uses the proportionated stratified random sampling method. Data were analyzed by multiple linear regression and R / C analysis. The results showed that simultaneously the factors that influence vegetable farming income had a significant effect on income at a trust level of 89%. Partially, fertilizer costs, pesticide costs, labor costs, education levels, and prices have a significant effect on income. The income contribution of vegetable farmers to the total income of farmer families is 80.02%. The value of R / C is 2.54, which means that vegetable farming is feasible financially. Keywords: income factors, vegetables, farming